Studying global pentecostalism: theories and methods - Anderson, Allan Heaton; Droogers, André; Laan, Cornelis van der; Bergunder, Michael (University of California Press, 2010)
Frontmatter -- Contents -- Abbreviations -- Introduction / Anderson, Allan / Bergunder, Michael / Droogers, André / van der Laan, Cornelis -- Part 1. Interdisciplinary Perspectives -- 1. Varieties, Taxonomies, and Defi nitions / Anderson, Allan -- 2. Essentialist and Normative Approaches / Droogers, André -- 3. The Cultural Turn / Bergunder, Michael -- 4. Gender and Power / Brusco, Elizabeth -- 5. Conversion Narratives / Gooren, Henri -- 6. Pentecostalism and Globalization / Meyer, Birgit -- Part 2. Social Sciences and Humanities -- 7. Psychology of Religion / Huber, Stefan -- 8. Anthropology of Religion / Robbins, Joel -- 9. Sociology of Religion / Hunt, Stephen -- 10. Historical Approaches / van der Laan, Cornelis -- Part 3. Theology -- 11. Pneumatologies in Systematic Theology / Kärkkäinen, Veli-Matti -- 12. Missiology and the Interreligious Encounter / Yong, Amos / Richie, Tony -- 13. Practical Theology / Cartledge, Mark J. -- 14. Ecumenism / Robeck Jr., Cecil M. -- Contributors -- Index
Keywords: Aufsatzsammlung; Pfingstbewegung